Ex Post Impacts of Chashma Right Bank Irrigation Project on Cropping Pattern in D.I. Khan district, Pakistanc - Atta-ur-Rahman; Amir Nawaz Khan (Journal of Basic & Applied Sciences, 2021)
This paper carries out the ex post environmental impacts of Chashma Right Bank Irrigation Project (CRBIP) on the cropping pattern of district D.I. Khan, Pakistan. Work on the Chashma Right Bank Canal (CRBC) was started in 1984 and subsequently completed in three stages during 2003-2004. The total cultivable command area of CRBC is 250,000 ha. It commands only left bank area as the slope is from west to east. It spreads over the two provinces i.e. Khyber Pakhtunkhwa and Punjab. The ultimate goal of the CRBIP was to enhance agricultural productivity, employment opportunities and alleviate poverty. The analysis revealed that there had been large scale changes in the agricultural system, with the construction of CRBC in the arid tract of district D.I. Khan. These changes were both positive and negative. After the advent of CRBC, acreage of both Kharif (summer) and Rabi (winter) crops has improved. The analysis revealed that positive changes have occurred in rice, sugarcane, pulses, wheat, barley, orchards and vegetables. Contrary to this, negative changes were registered in sorghum, millet, oilseed, barley and maize. While comparing the ex post changes in the cropping system, new water loving crops has been introduced as a result of CRBC. It has directly affected the water-table. It was found from the analysis that water-table is inclining at a rapid pace and is serious threat to the crop area.